Comparative Transcriptome Analysis Reveals the Mechanism Associated With Dynamic Changes in Meat Quality of the Longissimus Thoracis Muscle in Tibetan Sheep at Different Growth Stages - Wen, Yuliang; Li, Shaobin; Bao, Gaoliang; Wang, Jiqing; Liu, Xiu; Hu, Jiang; Zhao, Fangfang; Zhao, Zhidong; Shi, Bingang; Luo, Yuzhu (Frontiers in Veterinary Science, 2022)
Tibetan sheep is one of the dominant populations at Qinghai-Tibet Plateau. Its meat is not only essential for the local people, but is preferred by the non-inhabitant of this plateau also. To investigate the salient development features and molecular mechanism of the meat difference of LT muscle caused by different growth stages in Tibetan sheep, the carcass performance, meat quality and comparative transcriptome analysis were performed for investigating the potential molecular mechanism of the meat quality difference of the LT muscle caused by different growth stages in the Tibetan sheep. A total of sixteen female Tibetan sheep including 4-months-old (4 m), 1.5-years-old (1.5 y), 3.5-years-old (3.5 y), and 6-years-old (6 y) were selected. The shear force increased with the increase of age (P < 0.05), while the intramuscular fat (IMF) was the highest at 1.5 y. The AMPK signaling pathway was significantly enriched in the four comparative groups. The hub genes P4HA2, FBXL4, PPARA were identified to regulate the meat quality using the weighted gene co-expression network analysis (WGCNA). In summary, 1.5 y was found to be the most suitable slaughter age of the Tibetan sheep which ensured better meat tenderness and higher IMF content. Moreover, the genes LIPE, LEP, ADIPOQ, SCD, FASN were found to be possibly involved in the AMPK signaling pathway for regulating the transformation of the muscle fiber types, further influencing the meat quality.